The European banking union and constitution beacon for advanced integration or death-knell for democracy? - Grundmann, Stefan 1958-; Micklitz, Hans-W (Hart Publishing, 2019)
"In 2012, at the height of the sovereign debt crisis, European decision makers pushed for developing an 'ever closer union' with the formation of a European Banking Union (BU). Although it provoked widespread debate, to date there has been no coherent discussion of the political and constitutional dimensions of the European Banking Union. This important new publication fills this gap. Drawing on the expertise of recognized experts in the field, it explores banking union from legal, economic and political perspectives. It takes a four part approach; firstly setting the scene by examining the constitutional foundations of banking union. It then looks at its implications for European integration and for democracy. Finally it asks whether it might be more usefully regarded as a trade-off between integration and democracy. This is an important, timely and authoritative collection"--Provided by publisher.